Unreliable Network Re-Authentication Protocol Based On Hybrid Key Using CSP Approach. - Ramadass, Sureswaran; Budiarto, Rahmat; Ho, Cheah Luan (Dr. Sang H. Lee, 2007)
Network security is becoming increasingly vital in today's fast growing mobile computing environment. Due to constraints in device size and portability, limited processing power, small disk capacity, intermittent network disconnections and frequent switching between network access points have been observed in mobile devices.